Optimization of interaction between human and techniques at the space vehicle - K A Pupkov; A D Ustyuzhanin (RUDN Journal of Engineering Research, 2010)
The problem of control system synthesis with a human operator in a loop of control is considered. The optimal transfer function calculation method based on Pade approximation for the human operator is presented.